2008
DOI: 10.1089/ten.tea.2007.0186
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Tissue Engineering of Anatomically Shaped Implants via MRI and Micro-CT Using Injection Molding

Abstract: This study demonstrates for the first time the development of engineered tissues based on anatomic geometries derived from widely used medical imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI). Computer-aided design and tissue injection molding techniques have demonstrated the ability to generate living implants of complex geometry. Due to its complex geometry, the meniscus of the knee was used as an example of this technique's capabilities. MRI and microcomputed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 44 publications
2
137
0
Order By: Relevance
“…32 Briefly, three samples were collected from each of the frozen 6-month ears, previously studied 1-and 3-month ears, 25 and native juvenile bovine ears. Samples were weighed, refrozen, lyophilized, and weighed again.…”
Section: Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Briefly, three samples were collected from each of the frozen 6-month ears, previously studied 1-and 3-month ears, 25 and native juvenile bovine ears. Samples were weighed, refrozen, lyophilized, and weighed again.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Resultant stresses were recorded at 1 Hz and the temporal profiles of stress were fit to a poroelastic model of tissue behavior using custom MATLAB (MathWorks, Natick, MA) code to calculate the equilibrium modulus and hydraulic permeability. 32 …”
Section: Mechanical Analysismentioning
confidence: 99%
“…27 In fact for several years, µ-CT has been a standard tool for biomechanical evaluation and optimization in orthopedic surgery. Jaecques et al 28 even examined the postimplantation adaptation of bone tissue by µ-CT.…”
Section: Discussionmentioning
confidence: 99%
“…Their semi-liquid nature allows engineering anatomic geometries derived from medical imaging techniques, such as computed tomography or magnetic resonance, by the use of custom-printed moulds (Ballyns et al, 2008). Promising results were reported with alginate (Ballyns et al, 2010;Ballyns et al, 2008) and polyvinyl alcohol (PVA) (Kobayashi et al, 2003;Kobayashi et al, 2005). However, despite their wide implementation in cartilage tissue engineering they have been hardly utilised for meniscus engineering.…”
Section: Scotti Et Al Meniscus Repair and Regenerationmentioning
confidence: 99%
“…In particular, because of its complex geometry, meniscus engineering can benefit from computer-aided design and tissue injection moulding techniques. Ballyns et al (2008) demonstrated the feasibility of this approach by engineering a critically sized meniscus with bovine and ovine fibrochondrocytes suspended in agarose hydrogel. Even if the cells were not of human origin, this is an important proof of principle, opening new possibilities in meniscus tissue engineering.…”
Section: Total Meniscus Engineeringmentioning
confidence: 99%